Influência da extensão e tipo de retentor intra-radicular na deformacão e resistência à fratura de dentes tratados endodonticamente - Santos Filho, Paulo César de Freitas (2007)
Studies concerning the effects of different post systems insertion depth on the strain and fracture resistance of endodontically treated teeth remain controversial. The purpose of this study was to investigate in vitro the effects of different post systems and depth of post insertion on the strain and fracture resistance of endodontically treated bovine incisors. One hundred thirty-five freshly extracted bovine incisors were sectioned 15 mm from their apices, endodontically treated and divided into 3 groups (n=45): GFP, glass fiber post; PSP, prefabricated steel post; CMC, cast metal core. Each group was divided into 3 subgroups (n=15) according to the post lenght: 5.0 mm; 7.5 mm; 10.0 mm. All teeth were restored with complete metal crowns. In the strain-gauge measurement were used two strain-gages for tooth bonded in one proximal and buccal surfaces of the tooth. Microstrain values (μS) were obtained and related of fracture resistance. The fracture resistance (N) was measured in a universal testing machine at 45 degrees to the long axis of the tooth until failure. The data were analyzed with 2-way analyses of variance, followed by the Tukey HSD test (α=.05). Fracture modes were recorded based on the degree of tooth structure and restoration damage. The results showed that microstrain was always higher in buccal surface than lingual surface in any post and length. In metallic posts with 5.0 mm length resulted in increased strain, mainly in proximal surface. The 2-way analyses showed that the post length was statistically significant for the metallic post. In length of 10.0 mm the CMC showed the highest fracture resistance. However, the GFP showed no statistically difference in fracture resistance in 3 post length. The root fractures were observed in CMC and PSP. In GFP was observed almost every fracture in the resin core and post.